2007
DOI: 10.1111/j.1365-2885.2007.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the adverse effects of oral firocoxib in healthy dogs

Abstract: This study evaluated the adverse effects of oral firocoxib in dogs. Six dogs (20.2+/-6.3 kg) were studied. Values for complete blood count (CBC), serum urea, creatinine, alanine transaminase, alanine phosphatase, gamma-glutamyl transferase, occult blood in feces, platelet aggregation, and buccal mucosal bleeding time were measured before and 7, 14, 21, and 29 days after SID treatment with firocoxib 5.3+/-0.34 mg/kg (FG) or lactose 1 mg/kg (LG) for 28 days, in a randomized crossover study. Gastrointestinal (GI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 27 publications
3
30
1
4
Order By: Relevance
“…This NSAID, firocoxib, has been shown to be a highly selective inhibitor of COX-2 in the horse with a COX selectivity ratio of 265 (McCann et al 2002). In a clinical study, firocoxib was not associated with an increased risk of adverse gastrointestinal effects in the dog (Steagall et al 2007).…”
Section: Small Intestinementioning
confidence: 90%
See 1 more Smart Citation
“…This NSAID, firocoxib, has been shown to be a highly selective inhibitor of COX-2 in the horse with a COX selectivity ratio of 265 (McCann et al 2002). In a clinical study, firocoxib was not associated with an increased risk of adverse gastrointestinal effects in the dog (Steagall et al 2007).…”
Section: Small Intestinementioning
confidence: 90%
“…2002). In a clinical study, firocoxib was not associated with an increased risk of adverse gastrointestinal effects in the dog (Steagall et al . 2007).…”
Section: Effect Of Nsaids On Recovery Of Barrier Functionmentioning
confidence: 99%
“…In a long-term study over 52 weeks of treatment, a slight increase in withdrawal rate (5.1%) was reported due to GI signs (Autefage et al, 2011). Steagall et al (2007) evaluated the adverse effects of oral firocoxib in healthy dogs for 29 days and found that a dose of 5.3±0.34 mg kg −1 of firocoxib did not cause any adverse effects on the GI tract or serum biochemical variables and was well tolerated in terms of hematological signs including platelet aggregation and buccal mucosal bleeding time index (Steagall et al, 2007). Firocoxib was found to be effective in a 90 day Science Publications AJAVS long-term study performed on relatively geriatric dogs (over 7 years) affected by osteoarthritis.…”
Section: Firocoxibmentioning
confidence: 99%
“…The dogs were evaluated for 40 days after treatment began and the incidence of adverse gastrointestinal effects was low (3%), although adverse effects were evaluated on an observational basis rather than by using more detailed monitoring. In a more detailed experimental study, Steagall et al, (2007) evaluated oral firocoxib for one month in six healthy dogs. Blood biochemistry and buccal mucosal bleeding times, as well as gastrointestinal endoscopy, were carried out to evaluate the adverse effects of the drug in this experimental model.…”
Section: Is Firocoxib Associated With Reduced Adverse Effects Comparementioning
confidence: 99%